MEASUREMENT OF STUDENT ACHIEVEMENT DURING THE COVID-19 PANDEMIC - Zaenal Arifin; Nia Kania (Gammath : Jurnal Ilmiah Program Studi Pendidikan Matematika, 2022)
This study aims to measure student learning achievement during the covid-19 pandemic, and to find out whether the instrument used is valid and reliable. This research was conducted in class XII IPA 1 MAN 3 Cianjur. The results showed that the percentage with very high validity was 44%, the percentage with high validity was 44%, and the percentage with high validity was 12%. This shows that all instruments measuring student achievement during the covid-19 pandemic are valid. In addition, the results of the reliability estimation based on the tested data are 0.7619. That is, the instrument made is reliable, so this instrument can be used in any class or on other subjects. In general, the results of the analysis of all student scores show that student learning achievement in the trial of 64.86% has good learning achievement, and 35.12% has poor learning achievement. During this COVID-19 pandemic, of course, there are many factors that affect student achievement, and this can be used as material for further research.Keywords: Covid-19 Pandemic, Measurement, Reliability, Student Achievement, Validity.